MARKETING STRATEGY DEVELOPMENT TO INCREASE MARKET SHARE IN THE SRAGEN BATIK MSMES CENTER - Pratiwi, Adcharina; Adhitama, Rizky Ramadhan Aprian; Dewi, Calista Rosyita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research focuses on the creative economy and the criteria for marketing strategy in the sociopreneurial sector. The research was conducted in accordance with the planned roadmap for the Masaran batik industry center in Sragen. The research sample was Dewi Ratih MSME in the Masaran area of Sragen. This research was motivated by several problems, namely: (1) suboptimal marketing strategies, (2) unstable batik sales volume that often declines at certain times, and (3) less than optimal business profitability. This research is highly urgent for business actors and batik industry center associations as a solution to address these issues. The research resulted in the formulation of a superior marketing strategy model and plan that is competitive in the batik industry. The results of this research will be used as a formulation and utilized by Sragen batik MSMEs, students, lecturers, the community, and similar entrepreneurs to develop effective marketing strategies. This research aims to solve this problem through a goodness of fit model design approach, which is implemented as a solution to improve marketing strategy, sales volume, and business profit. The research resulted in the formulation of a marketing strategy model, sales volume, and market share that can increase the profitability of batik businesses. Keywords: product, price, promotion, distribution, sales volume